Inflammatory reaction to the human bot-fly, Dermatobia hominis, in infested and reinfested mice - Lello, E.; de Rosis, AMB (Blackwell Publishing, 2003)
Two groups of mice were infested with first stage larvae of the human bot-fly, Dermatobia hominis (Linnaeus Jr) (Diptera: Oestridae). In the first group, skin biopsies were carried out 1, 3, 5, 7, 10 and 18 days after infestation. The second group was also infested but had all the larvae removed 5 days after infestation. The mice in the latter group were reinfested 4 weeks later and skin biopsies were carried out 1, 3, 5, 7, 10 and 18 days after reinfestation. In the first group, an inflammatory reaction began slowly, the neutrophils being the main inflammatory cells, eosinophils being scarce. The reaction progressed with time, developing a necrotic halo around the larvae containing inflammatory cells surrounded by fibroblasts. The inflammation invaded the adjacent tissue. In the second group, the inflammatory reaction was intense on the day immediately after reinfestation, the pattern being changed by the presence of a large number of eosinophils. Activated fibroblasts surrounding the necrotic area around the larvae appeared 3 days after reinfestation in the second group and 7 days after infestation in the first group. The results demonstrated that the previous contact with the antigens elicited the early arrival of eosinophils, probably through the chemotactic factors liberated by mast cells in the anaphylactic reaction.
Keywords: Dermatobia hominis; eosinophils; inflammation; mice; neutrophils